Social capital and pneumococcal vaccination (PPSV23) in community-dwelling older Japanese: a JAGES multilevel cross-sectional study - Katsunori Kondo; Yugo Shobugawa; Kousuke Iwai-Saito (BMJ Open)
Objective Inequalities exist between the 23-valent pneumococcal polysaccharide vaccination (PPSV23) rate in each municipality among Japanese older adults. Exploring individual-level and community-level intervenable factors is necessary to improve the vaccination rates. We examined the associations between community-level and individual-level social capital and the PPSV23 vaccination among older Japanese adults using multilevel Poisson regression analyses.Design Cross-sectional study.Setting We used data from the Japan Gerontological Evaluation Study, conducted between 3 October 2016 and 10 January 2017 in 631 districts, 39 municipalities and 18 prefectures.Participants The target population comprised persons aged 65 years or older who are physically and cognitively independent (that is, not certified as needing long-term care). Further, 180 021 older adults from 39 Japanese municipalities were enrolled.Primary outcome measure The primary outcome was the PPSV23 vaccination among the Japanese older adults aged 65 years or older who did not have physical or cognitive disabilities.Results After adjusting for municipality-, community-, individual-levels effects with multiple imputation, 137 075 individuals who participated in one/more of the civic participation (participation of social groups), social cohesion (social tie), or reciprocity (mutual exchange of social support) were significantly associated with more vaccinations than those without the three social capitals among the 137 075 older adults (13.0% (95% CI 11.0% to 14.9%), 5.0% (95% CI 2.4% to 7.6%) or 33.9% (95% CI23.6% to 44.2%) increase, respectively, p>0.001 for all). The rich (≥+1 SD) community-level civic participation was significantly associated with 3.4% increase [95% CI 0.02% to 6.78%, p<0.05] of the PPSV23 vaccination among the older adults compared to those with the poor or standard one.Conclusions Older adults with one/more of the three social capitals at the both levels received more PPSV23 vaccinations than those without those social capitals. Therefore, fostering of those social capitals may improve the inequality of the PPSV23 vaccination rate among older adults in each municipality.